Robotics : state of the art and future challenges - Bekey, George A., 1928- (Imperial College Press ; Distributed by World Scientific Pub. Co., 2008)
This book presents the results of an assessment of the state of robotics in Japan, South Korea, Western Europe and Australia and a comparison of robotics R & D programs in these countries with those in the United States. The comparisons include areas like robotic vehicles, space robotics, service robots, humanoid robots, networked robots, and robots for biological and medical applications, and based on criteria such as quality, scope, funding and commercialization. This important study identifies a number of areas where the traditional lead of the United States is being overtaken by developments in other countries.